Peran Jamaah Kerukunan sebagai Kearifan Lokal dalam Masyarakat Muslim Pedesaan - Umam, M. Nur Khotibul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study examines the phenomenon of Jamaah Kerukunan (Jamkur), a local religious community in Ranubedali Village, Lumajang, Indonesia, comprising members with diverse educational and religious backgrounds. The research aims to analyze how this community fosters social and religious cohesion through structured weekly activities, including congregational prayers, collective dhikr, and monthly thematic sermons. Adopting an ethnographic approach, the study utilizes participant observation, in-depth interviews, and documentation to capture the symbolic meanings behind these communal practices. The findings reveal that Jamkur serves as an embodiment of local wisdom that effectively promotes solidarity, compassion, and tolerance within a pluralistic rural Muslim society. By implementing a rotating meeting system and voluntary contributions, the community establishes a symbolic commitment to unity that transcends individual differences in religious understanding. Consequently, Jamkur provides an inclusive, egalitarian learning space that mitigates social friction. Ultimately, the community represents a practical model of Islam rahmatan lil-‘alamin (Islam as a blessing to all creation), demonstrating how localized religious institutions can maintain social harmony and peace in a contemporary Indonesian context.